Socialization and Training of Scientific Journal Article Writing Strategy for Teachers - Dwi Agus Kurniawan; Darmaji Darmaji; Astalini Astalini; Asrial Asrial; Syahrial Syahrial; Raden Muhammad Afrialdi; Sarah Pramitha (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to explore the understanding and effectiveness of teachers' responses to the socialisation and training on scientific article writing strategies at Al-Hidayah Foundation. Methodology: The research method used in this study is a quantitative method with a descriptive statistical approach. Data collection was carried out through questionnaires and questionnaires distributed to teachers participating in training and socialization. The questionnaire was designed to measure initial understanding, changes in perception, and increased ability to write scientific articles before and after training. The data analysis technique used descriptive statistics assisted by SPSS. Main Findings: This socialisation and training is designed to improve teachers' skills and knowledge in writing publishable scientific articles, motivated by the need to improve the quality of education and learning in schools, teachers are expected not only to act as teachers but also as researchers who actively contribute to the development of science, with the socialisation of this training it was found that some teachers were still confused about how to compile good and correct scientific articles. Novelty/Originality of this study: This research introduces a new training method or strategy, this research includes an evaluation or analysis of the impact of the training. Overall, this research can advance knowledge by providing a new model or approach in scientific writing training for teachers, as well as offering new insights that can be applied in broader educational context.